Sosialisasi dan Edukasi Pencegahan Pernikahan Dini pada Siswa Sekolah Dasar di Desa Sumbersari - Lifriana Zahwa Nabila; Aprilia Suryan Dini; Sefanah Dwi Rahma; Auliya Sugiarti; Shevilia Mary Anggeline; Suhariyati Suhariyati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Sumbersari Village is one of the few places where child marriage is still a problem. Children's mental health, education, and future prospects are all negatively impacted by this practice. The KKN (Community Service Program) group organizes community service projects that teach fifth and sixth graders about the dangers of child marriage and give them the opportunity to socialize. One of the strategies used is a question and answer session with incentives to increase student engagement, as well as presenting material in simple language and facilitating interactive conversations. The results show that students' interest and knowledge about child marriage risks increases. This activity has limitations due to its limited reach, especially for elementary school children, and the relatively basic nature of the subject matter. Therefore, for initiatives to combat child marriage to be more successful and sustainable, follow-up programs involving parents, adolescents, and community leaders are essential. Collaboration with relevant parties is needed to create deeper policies, as well as increase awareness of the importance of women's education and empowerment in preventing child marriage.